Wave Characteristics of Magnetic Pi2 Pulsations in the Auroral Region─Spectral and Polarization Studies - Kuwashima, Masayuki (1978)
P(論文) Concurrent observations of geomagnetic variations by means of a fluxgate magnetometer and an induction magnetometer were carried out at Syowa (L = 6.3) and Mizuho Stations(L = 7.7) in Antarctica from August 29 to September 29, 1973. Spectral and polarization characteristics of the substorm-associated Pi2 pulsations are investigated in detail using the data obtained at Syowa and Mizuho as well as those at Mawson(L = 9.1), Sanae(L = 4), Hermanus (L = l.8) in the southern hemisphere and Reykjavik(L = 6.3) in the northern hemisphere. The Pi2 pulsations are observed simultaneously with the onset of a substorm expansion phase over the wide area from the auroral region to the low latitudes with a similar predominant period showing a primary amplitude maximum at the auroral oval and a secondary one near the plasmapause. Pi2 period is closely related to the location of the auroral breakup region in the following way that it becomes shorter(longer) when the auroral breakup occurs at lower(higher) latitude. The Pi2 data from the conjugate pair of stations, Syowa and Reykjavik, show that the H-components oscillate in phase, whereas the D-components oscillate out of phase suggesting that Pi2 waves observed in the auroral region are characterized as odd mode standing oscillations. The characteristics of Pi2 polarization change drastically across the center of the auroral electrojet. The sense of polarization reverses from a left-hand polarization on the lower latitude side of the auroral electrojet to a right-hand one on the higher latitude side before ～2lh MLT at which Pi2 maximum occurrence is observed and vice versa after ～21h MLT. Such polarization reversals result from large phase shifts(～180°) of the horizontal(north-south) components across the center of the auroral electrojet. If Pi2 waves propagate westward before the time of Pi2 maximum occurrence and eastward thereafter, the observed polarization reversals can be interpreted by the resonance theory of the coupled hydromagnetic waves. Considering these ...